Pentecostalismo xamânico: o modo Terena de ser pentecostal - Gonçalves, Iago Freitas (2018)
The Pentecostal movement became so expressive in the Brazilian religious scene that it reached the natives of Brazil, specifically the Terena people. They are especially in Brazilian Pantanal, in the state of Mato Grosso do Sul. This research will focus on studying the insertion of the Pentecostal movement within the Terena culture, specifically on Moreira village, located in Miranda-MS. On this village, the Pentecostal Christian influence on the Terena people is evidenced when the numbers of churches and the numbers of people that participate of this religious expression is analyzed. There are five churches, three Pentecostal, representing about twenty-five percent of the total population from the village. It is relevant to note that Christian influence is present among the Terena people more than a century and half since the Catolican arrival in the mid-nineteenth century. However, the Terena people kept personal characteristics, as your shamanic practice. Thus, two distinct religious expressions coexists. The focus of this research is the relationship of Shamanism-Pentecostalism based on bibliographic review and field research to investigate the ways that Shamanism and Pentecostalism have been appropriated on this religious field, what has generated a new way of being a Pentecostal, which was denominated as Pentecostalism Shamanic